Dimensional Tolerances and Length Determination of High-Strength Bolts - Swanson, James A.; Rassati, Gian Andrea; Larson, Chad M. (Engineering Journal, 2020)
Structural engineers and detailers are often removed from the process of manufacturing bolts, and thus the tolerances and variances that go along with common manufacturing processes. While this does not represent a problem in most cases, being familiar with the manufacturing processes and tolerances associated with high-strength bolts can help prevent some problems from occurring before the design process even begins, particularly when shorter bolt lengths are needed. This lack of familiarity, in some circumstances, might lead to mistaken assumptions regarding the location of the shear plane relative to the threads of the bolt, which may lead to incorrect designs. While an engineer might presume that bolt strength would not control in such short grips, this paper will discuss the cases in which this can become an issue. This paper summarizes the major variances between nominal and actual dimensions, evaluates some of the consequences that those variances can have on design, presents solutions to those issues, and culminates with a proposed design procedure for proper length determination of high-strength bolts with several illustrative examples.